2017
DOI: 10.17744/mehc.39.4.03
|View full text |Cite
|
Sign up to set email alerts
|

Complementary and Integrative Health Assessment for Practitioners Scale: Initial Development and Validation

Abstract: The Complementary and Integrative Health Assessment for Practitioners (CIHAP) scale was developed to assess counselors' and other health-care providers' current knowledge of complementary and integrative health (CIH) and their interest in integrating CIH into their practices. Participants included 493 counselors, counselor educators, human services professionals, and other health professionals. Exploratory and confirmatory factor analyses were conducted, along with measurement invariance, which was determined … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…The questionnaire comprised 26 questions with four sections: demographics (5 items), knowledge and attitudes to CIM (9 items) and medicinal cannabis (7 items), and knowledge of integrative oncology services within the hospital (6 items) (Online Resource 1 ). Questions were adapted from the validated Complementary and Integrative Health Assessment for Practitioners (CIHAP) which assesses HCPs current knowledge of CM and their interest in integrating CM into their practices [ 19 ]. Other questions were adapted from a survey used to understand oncologists’ practices around CM [ 20 ].…”
Section: Methodsmentioning
confidence: 99%
“…The questionnaire comprised 26 questions with four sections: demographics (5 items), knowledge and attitudes to CIM (9 items) and medicinal cannabis (7 items), and knowledge of integrative oncology services within the hospital (6 items) (Online Resource 1 ). Questions were adapted from the validated Complementary and Integrative Health Assessment for Practitioners (CIHAP) which assesses HCPs current knowledge of CM and their interest in integrating CM into their practices [ 19 ]. Other questions were adapted from a survey used to understand oncologists’ practices around CM [ 20 ].…”
Section: Methodsmentioning
confidence: 99%
“…Complementary and Integrative Health Assessment for Practitioners Scale (CIHAP): It was developed by Berger and Johnson (4,28). The scale assesses practitioners' current knowledge of complementary and integrative health and their interest in integrating them into their practice.…”
Section: Study Populationmentioning
confidence: 99%
“…High scores on the CAMBI indicated that the individual had strong beliefs about CAM use. CAMBI has been shown to have satisfactory reliability (Berger & Johnson, 2017;Grzywacz et al, 2012). Cronbach's alpha for the CAMBI was 0.81, and for natural treatments, preference for participation in health treatments, and orientation toward holistic health subscales were 0.75, 0.68, and 0.73, respectively.…”
Section: Complementary and Alternative Medicine Beliefs Inventorymentioning
confidence: 99%